VD_FINDINFO HC / 2011 / 131 vom 14. März 2011 - VD Tribunal cantonal (2011)
DIVORCE, MESURE PROVISIONNELLE, LOGEMENT DE LA FAMILLE, OBLIGATION D'ENTRETIEN, ENFANT, CONJOINT | 137 al. 2 CC, 163 CC, 176 al. 1 ch. 1 CC, 176 al. 1 ch. 2 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 310 CPC (CH)